1998
DOI: 10.1590/s1516-89131998000300003
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of β-Fructosidase with inulinase activity from Aspergillus niger - 245

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Also, at 70ºC, the lipase activity decreased to about 40% within 120 minutes of incubation. This was similar to the in which lipase production showed maximum activity at 50°C in et al [36] also reported that the enzyme activity declined as the temperature was gradually increased from 30 o C. This is because temperature affects the metabolic activity of microbial cells. Etabilli and ] also reported that denaturation of enzymes occurs when the temperature is high.…”
supporting
confidence: 86%
“…Also, at 70ºC, the lipase activity decreased to about 40% within 120 minutes of incubation. This was similar to the in which lipase production showed maximum activity at 50°C in et al [36] also reported that the enzyme activity declined as the temperature was gradually increased from 30 o C. This is because temperature affects the metabolic activity of microbial cells. Etabilli and ] also reported that denaturation of enzymes occurs when the temperature is high.…”
supporting
confidence: 86%